Click Synthesis Enabled Sulfur Atom Strategy for Polymerization‐Enhanced and Two‐Photon Photosensitization. Issue 21 (23rd March 2022) - Li, Chongyang; Liu, Junkai; Hong, Yingjuan; Lin, Runfeng; Liu, Zicheng; Chen, Ming; Lam, Jacky W. Y.; Ning, Guo‐Hong; Zheng, Xiuli; Qin, Anjun; Tang, Ben Zhong
Abstract: Facile tailoring of photosensitizers (PSs) with advanced and synergetic properties is highly expected to broaden and deepen photodynamic therapy (PDT) applications. Herein, a catalyst‐free thiol–yne click reaction was employed to develop the sulfur atom‐based PSs by using the in situ formed sulfur "heavy atom effect" to enhance the intersystem crossing (ISC), while such an effect can be remarkably magnified by the polymerization. The introduction of a tetraphenylpyrazine‐based aggregation‐induced emission (AIE) unit was also advantageous in PS design by suppressing their non‐radiative decay to facilitate the ISC in the aggregated state. Besides, the resulting sulfur atom electron donor, together with a double‐bond π bridge and AIE electron acceptor, created a donor‐π‐acceptor (D‐π‐A) molecular system with good two‐photon excitation properties. Combined with the high singlet oxygen generation efficiency, the fabricated polymer nanoparticles exhibited an excellent in vitro two‐photon‐excited PDT towards cancer cells, therefore possessing a huge potential for the deep‐tissue disease therapy. Abstract : A catalyst‐free thiol–yne click reaction facilely afforded photosensitizers by using the in situ formed sulfur "heavy atom effect" to enhance the intersystem crossing. Combined with aggregation‐induced emission and polymerization effects, excellent photosensitizers can be obtained for two‐photon excited photodynamic therapy.